GERAKAN SEKOLAH SADAR AKAN PENTINGNYA SARAPAN SEHAT TERHADAP PERFORMA BELAJAR PARA SISWA DI SDN 1 TALAGA - Anindia Hermawan, Belya; Adini Nurkarimah, Rizkya; Hipdilhak, Hifaz Nur; Pitriani, Karina; Lulu Humairoh; Vanni Rusdianti; Nabila Putri Ramdhania Arsyad; Arzheta Delfiena Larossa; Meutia Az Zahra; Lubis, Novriyanti (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
This outreach activity was carried out as an effort to increase elementary school children's knowledge and understanding of the importance of a healthy breakfast containing balanced nutrition on learning performance at school. The material provided is delivered through three methods, namely print media in the form of brochures, lecture methods supported by PowerPoint slides, and audio-visual media in the form of animated videos. The results of the counseling showed that the percentage of students' understanding of the importance of getting used to a healthy breakfast before the socialization was carried out was 69% and after the socialization was 94%. When applied in breakfast activities, the percentage obtained was 28% of students having breakfast, 23% of female students having breakfast, 8% of students not having breakfast and 41% of female students not having breakfast. The students' understanding of the side effects of not having breakfast before the socialization was 43% and after the socialization it was 57%. The level of students' understanding of the definition of balanced nutrition before and after socialization was carried out showed the same percentage, namely 50%. Based on the data obtained, the students' understanding of the definition of balanced nutrition before and after socialization was quite good. After the socialization activities, there was an increase in students' understanding of the importance of a healthy breakfast on learning performance, indicating that the students quite understood the counseling provided. This shows that the results of these outreach activities can help increase the implementation of SDN 1 Talaga students in breakfast activities before going to school. — Kegiatan penyuluhan ini dilakukan sebagai upaya meningkatkan pengetahuan dan pemahaman anak sekolah dasar tentang pentingnya sarapan sehat yang mengandung gizi seimbang terhadap performa belajar di sekolah. Penyampaian materi yang diberikan melalui tiga metode yaitu media cetak berupa pemberian brosur, metode ceramah yang didukung oleh slide PowerPoint, dan media audio-visual dalam bentuk video animasi. Hasil penyuluhan menunjukan persentase pemahaman siswa terhadap pentingnya membiasakan sarapan sehat sebelum sosialisasi dilakukan sebanyak 69% dan sesudah sosialisasi sebanyak 94%. Pada penerapannya dalam kegiatan sarapan diperoleh persentase sebanyak 28% siswa sarapan, 23% siswi sarapan, 8% siswa tidak sarapan dan 41% siswi tidak sarapan. Dalam pemahaman siswa-siswi terhadap efek samping tidak sarapan sebelum sosialisasi sebanyak 43% dan sesudah sosialisasi sebanyak 57%. Dalam tingkat pemahaman siswa-siswi mengenai definisi gizi seimbang sebelum dan sesudah sosialisi dilakukan menunjukkan persentase yang sama banyak, yaitu sebesar 50%. Berdasarkan hasil data yang diperoleh, pemahaman siswa-siswi terhadap definisi gizi seimbang sebelum dan sesudah sosialisasi cukup baik. Setelah kegiatan sosialisasi, adanya peningkatan pemahaman siswa-siswi tentang pentingnya sarapan sehat terhadap performa belajar menandakan siswa-siswi cukup paham terhadap penyuluhan yang diberikan. Hal ini menunjukkan bahwa hasil kegiatan penyuluhan tersebut dapat membantu meningkatkan penerapan siswa–siswi SDN 1 Talaga dalam kegiatan sarapan sebelum berangkat ke sekolah.